The Influence of Corporate Social Responsibility on Company Value Mediated by Environmental Performance - Ng, Suwandi; Mardiana, Ana; Ottong, Ervina (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2024)
Purpose – The purpose of this study was to analyze the effect of corporate social responsibility on firm value mediated by environmental performance. Design/methodology/approach – The type of research used is explanatory. This research uses purposive sampling method in sampling technique. Findings – The results of this study indicate that corporate social responsibility has a positive and significant effect on environmental performance. Environmental performance has a positive and significant effect on firm value. Corporate social responsibility has a positive and significant effect on firm value. Corporate social responsibility on company value can be mediated by environmental performance. Originality – The sample used in this study are non-financial companies listed on the Indonesia Stock Exchange in 2016-2020 which publish annual reports and sustainability reports, respectively. Keywords: Corporate social responsibility, Environmental Performance, Corporate Value Paper Type Research Result